Ocena skuteczności i bezpieczeństwa farmakoterapii inhibitorami aldosteronu w niewydolności serca = Evaluation of the efficacy and safety of pharmacotherapy using aldosterone antagonists in heart failure - Tarczykowska, Agata; Kochański, Bartosz; Wołowiec, Łukasz; Surowiec, Agnieszka; Plaskiewicz, Anna; Zukow, Walery (Journal of Education, Health and Sport, 2015)
Tarczykowska Agata, Kochański Bartosz, Wołowiec Łukasz, Surowiec Agnieszka, Plaskiewicz Anna, Zukow Walery. Ocena skuteczności i bezpieczeństwa farmakoterapii inhibitorami aldosteronu w niewydolności serca = Evaluation of the efficacy and safety of pharmacotherapy using aldosterone antagonists in heart failure. Journal of Education, Health and Sport. 2015;5(7):153-162. ISSN 2391-8306. DOI 10.5281/zenodo.19339 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%287%29%3A153-162 https://pbn.nauka.gov.pl/works/578965 http://dx.doi.org/10.5281/zenodo.19339 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 21.04.2015. Revised 28.05.2015. Accepted: 30.06.2015. Ocena skuteczności i bezpieczeństwa farmakoterapii inhibitorami aldosteronu w niewydolności serca Evaluation of the efficacy and safety of pharmacotherapy using aldosterone antagonists in heart failure Agata Tarczykowska1, Bartosz Kochański2, Łukasz Wołowiec3, Agnieszka Surowiec3, Anna Plaskiewicz2, Walery Zukow4 1Studenckie Koło Naukowe Biomed, Wydział Inżynierii Mechanicznej, Uniwersytet Technologiczno-Przyrodniczy, Bydgoszcz 2Katedra i Klinika Rehabilitacji, Wydział Nauk o Zdrowiu, Uniwersytet Mikołaja Kopernika w Toruniu 3Studenckie Koło Naukowe Diagnostyki i Terapii Niewydolności Serca, II Katedra Kardiologii, Collegium Medicum im. Ludwika Rydygiera w Bydgoszczy, Uniwersytet Mikołaja Kopernika w Toruniu 4Wydział Kultury Fizycznej, Zdrowia i Turystyki, Uniwersytet Kazimierza Wielkiego w Bydgoszczy Streszczenie Liczne badania udowodniły udział aldosteronu w patogenezie schorzeń układu krążenia. Aldosteron jest jednym z głównych czynników progresji niewydolności i remodelingu lewej komory. Pomimo stosowania inhibitorów konwertazy angiotensyny (ACE-I) lub inhibitorów receptorów dla angiotensyny II (ARB), negatywny wpływ układu RAA nie jest w pełni blokowany. Zjawisko nadmiernego wzrostu poziomu aldosteronu, pomimo stosowania ACE-I i ARB, zachodzi u około 40% chorych z niewydolnością serca. Pojawia się coraz więcej dowodów na to, jak ważne jest w tym wypadku dodatkowe zablokowanie receptorów mineralokortykoidowych. Obecnie dostępne są już na rynku inhibitory aldosteronu, zarówno selektywny eplerenon jak i nieselektywny spironolakton. Abstract Numerous tests have proved the influence of aldosterone on pathogenesis of cardiovascular system. Aldosteron is one of the main factors that cause the progress of heart failure and left ventricular remodeling. Although angiotensin-converting enzyme and angiotensin II receptor blockers are used, the negative influence of RAAS is not fully blocked. Despite the use of ACE inhibitors and ARBs, too high aldosterone level occurs in approximately 40% of patients with heart failure. There are many evidences that in this case also very important is to block mineralocorticoid receptors. Nowadays aldosterone antagonists are available on the drug market, both selective eplerenone and non-selective spironolactone. Słowa kluczowe: niewydolność serca, inhibitory aldosteronu, spironolakton, eplerenon. Keywords: heart failure, aldosterone antagonists, spironolactone, eplerenone.